Engagement Markers in Discussion Section of Research Articles Written by English Education Students and Articles Published in Reputable English Journal - Suri Aisyah; Mei Hardiah; Muhammad Fadhli (Journal of English Education and Teaching, 2022)
Some studies concerned about engagement markers (EMs) have been conducted among international authors. However, it does not literally trigger Indonesian scholars to study this discipline. Based on this fact, this research aimed to compare EMs in the discussion section of research articles (RAs) written by English Education students of Bengkulu University and RAs published in a reputable English journal. The corpora were analyzed by using the documentation checklist with a quantitative approach. The results showed that the more frequent types of EMs employed by students were knowledge appeals and directives. Similarly, experienced authors of RAs published in the reputable English journal employed the same dominant EMs. However, the order of minor prevalent markers in both corpora differed slightly. The Chi-square test result indicated that the differences in EMs between both corpora were significant in quantity (with Asymp sig. 0.000). More specifically, the experienced authors used a more considerable amount of EMs. In conclusion, the higher frequency of EMs in experienced writers’ RAs signifies the authors’ awareness of using EMs to construct relationships with readers. Therefore, it is essential to emphasize the use of EMs in academic writing. Further study is suggested to analyze the accuracy of EMs in the corpora and focus on a particular type of EMs for achieving more comprehensive findings.